Crowdfunding for SMEs A European Perspective - Bottiglia, Roberto; Pichler, Flavio; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
Crowdfunding for SMEs: A European Perspective provides a valuable insight into this new source of capital. In particular, the authors focus on financial return crowdfunding, which repays the crowd either through debt or equity. This source of capital might play a significant role in the future becoming an alternative or a complement to traditional funding sources. It is therefore of the uttermost importance to understand what has boosted its exponential growth in recent years, as well as the key drivers of success of P2P lending and equity crowdfunding campaigns on both the funders and the fundraisers side. Due to the financial nature of the return provided to the crowd, financial return crowdfunding has been the object of recent waves of regulation, although the European Union still lacks a set of common rules. The aim of regulation should be twofold, to protect investors and, at the same time, to favor the financing for SMEs. In this book, the authors explore such issues and the regulatory policies, while looking to the future of financial return crowdfunding as an evolving source of capital. .
Keywords: Capital investments; Capital market; Business enterprises-Finance.; Financial engineering; Finance, Public; European Union; Investment Appraisal